Cyclic di-GMP Signaling in Bacillus subtilis Is Governed by Direct Interactions of Diguanylate Cyclases and Cognate Receptors - Sandra Kunz (American Society for Microbiology, 2020)
ABSTRACT Bacillus subtilis contains two known cyclic di-GMP (c-di-GMP)-dependent receptors, YdaK and DgrA, as well as three diguanylate cyclases (DGCs): soluble DgcP and membrane-integral DgcK and DgcW. DgrA regulates motility, while YdaK is responsible for the formation of a putative exopolysaccharide, dependent on the activity of DgcK. Using single-molecule tracking, we show that a majority of DgcK molecules are statically positioned in the cell membrane but significantly less so in the absence of YdaK but more so upon overproduction of YdaK. The soluble domains of DgcK and of YdaK show a direct interaction in vitro, which depends on an intact I-site within the degenerated GGDEF domain of YdaK. These experiments suggest a direct handover of a second messenger at a single subcellular site. Interestingly, all three DGC proteins contribute toward downregulation of motility via the PilZ protein DgrA. Deletion of dgrA also affects the mobility of DgcK within the membrane and also that of DgcP, which arrests less often at the membrane in the absence of DgrA. Both, DgcK and DgcP interact with DgrA in vitro, showing that divergent as well as convergent direct connections exist between cyclases and their effector proteins. Automated determination of molecule numbers in live cells revealed that DgcK and DgcP are present at very low copy numbers of 6 or 25 per cell, respectively, such that for DgcK, a part of the cell population does not contain any DgcK molecule, rendering signaling via c-di-GMP extremely efficient. IMPORTANCE Second messengers are free to diffuse through the cells and to activate all responsive elements. Cyclic di-GMP (c-di-GMP) signaling plays an important role in the determination of the life style transition between motility and sessility/biofilm formation but involves numerous distinct synthetases (diguanylate cyclases [DGCs]) or receptor pathways that appear to act in an independent manner. Using Bacillus subtilis as a model organism, we show that for two c-di-GMP pathways, DGCs and receptor molecules operate via direct interactions, where a synthesized dinucleotide appears to be directly used for the protein-protein interaction. We show that very few DGC molecules exist within cells; in the case of exopolysaccharide (EPS) formation via membrane protein DgcK, the DGC molecules act at a single site, setting up a single signaling pool within the cell membrane. Using single-molecule tracking, we show that the soluble DGC DgcP arrests at the cell membrane, interacting with its receptor, DgrA, which slows down motility. DgrA also directly binds to DgcK, showing that divergent as well as convergent modules exist in B. subtilis. Thus, local-pool signal transduction operates extremely efficiently and specifically.